Detection of VLF Attenuation in the Earth‐Ionosphere Waveguide Caused by X‐Class Solar Flares Using aGlobal Lightning Location Network - T. S. Anderson; M. P. McCarthy; R. H. Holzworth (Space Weather)
Abstract Solar flares, energetic particles, and Earth‐impacting coronal mass ejections enhance ionization in the lower ionosphere, inhibiting radio wave propagation in the Earth‐ionosphere waveguide (EIWG). This enhanced ionization is observed locally by ionosondes and GPS/GNSS receivers, but spatial coverage of these observations is limited by receiver location. Very low frequency (VLF) propagation studies have previously been performed to assess the impact of space weather on the EIWG; however, these studies are typically limited by small numbers of fixed VLF transmitters and receivers and observe only the region of the EIWG along propagation paths between transmitters and receivers. Here, we use global lightning as a VLF source and an existing lightning detection network as a receiver. By mapping sferic propagation paths between lightning strokes and numerous network stations and considering how this distribution of paths changes during solar events, we can identify attenuation regions in the EIWG caused by space weather. We describe the VLF response in the EIWG to two X‐class solar flares and compare mapped attenuation regions with those provided by the NOAA D‐Region Absorption Prediction model. The identified attenuation regions associated with these flares match the D‐Region Absorption Prediction‐predicted regions well in both spatial extent and onset timing. Measurements of VLF attenuation caused by solar flares can provide ground‐truth confirmation of modeled attenuation and can inform the detection efficiency of lightning location networks. This analysis also paves the way for real‐time VLF attenuation mapping in the EIWG.